2022
DOI: 10.3390/bs12040096
|View full text |Cite
|
Sign up to set email alerts
|

Five Years after the Fort McMurray Wildfire: Prevalence and Correlates of Low Resilience

Abstract: Background: The Fort McMurray wildfire of 3 May 2016 was one of the most devastating natural disasters in Canadian history. Although resilience plays a crucial role in the daily functioning of individuals by acting as a protective shield that lessens the impact of disasters on their mental well-being, to date little is known about the long-term impact of wildfires on resilience and associated predictors of low resilience. Objectives: The objective of the study was to assess the prevalence and predictors of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Previous studies agree with our finding, which suggested that increased social support protects against mental health effects, increases resilience, and improves coping post-natural disasters [ 30 , 31 , 32 ]. Low levels of social support are also associated with post-disaster psychological symptoms and mental health disorders [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies agree with our finding, which suggested that increased social support protects against mental health effects, increases resilience, and improves coping post-natural disasters [ 30 , 31 , 32 ]. Low levels of social support are also associated with post-disaster psychological symptoms and mental health disorders [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…The survey measured PTSD symptoms using the PTSD Checklist Civilian (PCL-C) ( 32 , 33 ), a self-report scale that measures PTSD presence and severity. The 17-item checklist corresponds to the PTSD symptoms as stated by the Diagnostic and Statistical Manual (DSM-IV).…”
Section: Methodsmentioning
confidence: 99%
“…Previous Australian research found higher bushfire exposure and stress were the main predictors of clinical levels of psychological distress 3–4 years after the 2009 Victorian Black Friday bushfire and remained important predictors 10 years later (Bryant et al, 2014, 2021). Age and higher PTSD symptoms predicted fewer positive resilience characteristics 5 years after the Canadian Fort McMurray Wildfire (Adu et al, 2022). In the year following the 2019–2020 Australian bushfires, high levels of psychological distress were recorded (Usher et al, 2022), but predictors have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have often relied on small samples and lacked a comparison group. Factors predicting the absence of psychopathology or the presence of positive psychological outcomes include demographic characteristics such as being male, older, having higher education and higher income (Ikizer et al, 2016; Li et al, 2012; Ni et al, 2015; Silveira et al, 2021); the absence of pre-existing financial or clinical stressors (mental or physical health) (Adu et al, 2022; Ikizer et al, 2016; Ni et al, 2015); and experiencing lower disaster severity (Chan and Rhodes, 2014). Research has typically not assessed these predictors together to identify how they relate to both psychological distress and positive psychological outcomes, nor in the context of bushfires.…”
Section: Introductionmentioning
confidence: 99%